Technology transfer in Taiwan's Information Industry - Yu, Hui-Yun
Hui-Yun Yu and Kuang S. Yeh discusses the lessons learned from 44 information technology transfer projects.
Both a technology gap and a market gap hinder technology transfer between Taiwan research institutes and private firms, interviews with staff members reveal.
Many governments, aiming to elevate their country's competitiveness, have taken the initiative in participating in industrial R&D activities. Technology transfer is one of the favorite methods, whereby public research institutes are established to close technological gaps. Interviews with 48 professionals involved in information technology transfer projects in Taiwan revealed that two gaps-the gap in technology and the gap in market-between research institutes and firms in a technology transfer feedback loop are detrimental to the effectiveness of technology transfer. To increase the effectiveness : 1) Performance evaluation should access the result as well as the process of a technology transfer project; 2) Professional ethics codes should provide guidelines regarding conflict of interest, intellectual property rights, and related matters; 3) The number of participating private firms in a transfer project should be limited to 3-5.
Keywords: Technology transfer--Taiwan.